ANALISIS KURANGNYA KEMAMPUAN MAHASISWA DALAM MENGGUNAKAN MICROSOFT WORD DAN DAMPAKNYA TERHADAP PENYELESAIAN TUGAS KULIAH - Abdurrahman, Umar; Armando, Gali; Siregar, Wal Yunansyah; Munawwar, Muhammad; Ilham, Muhammad Naufal; Dalimunthe, Syairal Fahmy (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2025)
This research aims to analyze the factors that influence students' ability to use Microsoft Word at Medan State University. Data was obtained through a questionnaire filled out by 30 students with questions related to ICT learning in high school, difficulties faced in using Microsoft Word, level of knowledge regarding important features of Microsoft Word, and the main obstacles in improving the ability to use this application. The method used is a descriptive quantitative method with frequency and percentage analysis. The research results show that the lack of ICT learning in high school (60%) is the main factor causing the lack of skills in using Microsoft Word. In addition, the majority of students admitted that they often faced difficulties in using this application, even though they felt they had a fairly good knowledge of its features. The main obstacle faced is the lack of technological facilities and time to practice. These findings indicate the need to increase ICT learning in high schools and provide adequate facilities in tertiary institutions.